Designing Virtual Reality Systems The Structured Approach - Kim, Gerard Jounghyun; SpringerLink (Online service) (London : Springer London, 2005)
Virtual Reality (VR) is a field of study that aims to create a system that provides a synthetic experience for its users. Developing and maintaining a VR system is a very difficult task, requiring in-depth knowledge in many different disciplines, such as sensing and tracking technologies, stereoscopic displays, multimodal interaction and processing, computer graphics and geometric modeling, dynamics and physical simulation, performance tuning, etc. The difficulty lies in the complexity of having to simultaneously consider many system goals, some of which are conflicting. Designing Virtual Reality Systems is organized in such a way that it follows a spiral development process, and for each stage, describing the problem and possible solutions for each stage. Much more hands-on than other introductory books to virtual reality, this book provides concrete examples and practical solutions to the technical challenges in building a VR system by following a specific development methodology, instead of solely explaining the high level concepts. Part 1 covers the very basics in building a VR system in a systematic way and explains various technical issues in object modeling and scene organization. Part 2 dives into the core of virtual reality dealing with 3D multimodal interaction, designing for usable and natural interaction and creating realistic object simulation. Primarily written for first level graduate students, advanced undergraduate students and IT professionals will also find this unique and reader-friendly book a valuable guide.
Basics of Designing Virtual Reality Systems -- Introduction: Virtual Reality in a Nutshell -- Requirements Engineering and Storyboarding -- Object and Scene Modeling -- Putting It All Together -- Performance Estimation and System Tuning -- Creating the Virtual Reality -- Output Display -- Sensors and Input Processing -- 3D Multimodal Interaction Design -- Simulation I: Collision Detection -- Simulation II: Physics-Based Motion and Collision Response -- Virtual Characters.
Keywords: Computer science; Software engineering; User interfaces (Computer systems).; Computer simulation; Computer graphics; Multimedia systems; Computer Science; User Interfaces and Human Computer Interaction; Computer Imaging, Vision, Pattern Recognition and Graphics; Media Design; Software Engineering; Simulation and Modeling; Electronic books